XRD data from Palouse loess at site CLY-2, eastern Washington, USA - Nicholas E Bader; Elliot A Broze; Molly A Coates; McKenzie M Elliott; Gabriella E McGann; Sarah Strozyk; Russell F Burmester (PANGAEA, 2024)
These data are from samples gathered in 2016 from the CLY-2 site in eastern Washington, USA (Location: 46.3131, -118.4874, WGS84). The CLY-2 is a roadcut exposing a vertical face of the Palouse loess containing carbonate paleosol horizons and tephras. The samples were collected from a set of three stepped trenches into the roadcut about 10-20 m apart. Each trench was excavated to a depth of about a meter to expose a fresh surface; the final ~10 cm was excavated with non-ferrous digging tools. One sample from each depth was ground in a Spex mill and analyzed for bulk chemical composition using a Thermo Scientific Niton Xl3t GOLDD+ portable X-ray fluorescence analyzer with a benchtop test stand.